Digital Leadership in the Era of Industry 4.0: A Comprehensive Literature Review - Kardina Engelina Siregar; Naseem Akhter (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The advent of Industry 4.0 has revolutionized the landscape of leadership, emphasizing the critical role of digital leadership in navigating technological advancements and organizational transformations. This comprehensive literature review explores the evolving concept of digital leadership within the context of Industry 4.0, aiming to synthesize current research findings, identify emerging trends, and highlight best practices. Through a systematic analysis of peer-reviewed articles, books, and conference papers from the last decade, this study examines the key attributes, strategies, and impacts of digital leadership on organizational performance and innovation. The review reveals that effective digital leaders exhibit a combination of technological proficiency, visionary thinking, and adaptive management skills. Furthermore, it underscores the importance of fostering a digital culture, promoting continuous learning, and leveraging data-driven decision-making to drive organizational success. By providing a holistic understanding of digital leadership, this study offers valuable insights for academics and practitioners seeking to enhance leadership effectiveness in the digital age. The findings underscore the necessity for organizations to invest in leadership development programs that align with the demands of Industry 4.0, ensuring leaders are equipped to lead in a rapidly changing technological environment.